Effects of air discharge on bubble dynamics in vertically discharged bubble plumes. (15th March 2023) - Behzadipour, Arsalan; Azimi, Amir H.; Neto, Iran E. Lima
Highlights: The effect of air discharge on the mixing capacity of bubble plumes was tested. Effects of air discharge on bubble concentration and bubble interface area were studied. Bubble interfacial area and bubble size frequency were measured along the plume axis. Bubble parameters were independent of air discharge <35% of the water depth. The number of bubbles and their velocities increased non-linearly with air discharge. Bubble diameter increased by 32 % as air discharge quadrupled. Abstract: Vertically discharged bubble plumes have many applications in the industry and environment, such as aeration and sludge removal, gas and liquid mixture, and gas transfer enhancement. Circular nozzles mainly generate vertical bubble plumes and the ambient aeration requirement determines the design parameters such as nozzle size and air discharge. A series of laboratory experiments was performed to test the effects of air discharge on bubble dynamics by evaluating, bubble interfacial area, bubble size frequency, and other related parameters. Four air discharges were selected and bubble characteristics such as bubble mean velocity, bubble concentration, bubble mean diameter, and bubble size distribution were measured with a Bubble Refractive Instrument (RBI) probe. The results showed that bubble characteristics such as bubble interfacial area, bubble frequency, and bubble concentration/gas fraction significantly varied with the distance from the nozzle and all parameters gradually decreased afterwards. It was found that bubble parameters were independent of air discharge for x / H  < 0.35, and strong discharge dependency was observed for x / H  ≥ 0.35 where  ×  is the distance from the nozzle and H is the water depth. Experimental results indicated that as air discharge increased by four times, the mean bubble diameter increased by an average of 32 %. The direct correlation between air discharge and bubble frequency indicated that both the number of bubbles and their velocities increased non-linearly with air discharge. The effect of air discharge on the distribution of bubble turbulent intensity indicated a non-linear growth on the probability of higher ranges of turbulent intensity.